Dan liever dood! Over martelaren en hun religieuze drijfveren - Bakker, Henk; Lietaert Peerbolte, Bert Jan (Amsterdam University Press, 2022)
Martyrs have a special status in every religion. They are "heroes" who give their lives for their ideals. Their death acquires a symbolic meaning and its own story within their own religious tradition. There is no fixed definition of 'the' martyr, in every time and situation people give it its own meaning. However, the death of the martyr is always shocking and creates a deep duality. In Dan liever dood!, experts address how we deal with martyrdom in the traditions of the five major world religions. What is meant by ""martyrdom"" in Christianity, Judaism, Islam, Buddhism, and Hinduism? And in the secular world? Where does this talk of 'martyrs' come from, and how is their martyrdom valued?